A Case of Serotonin Syndrome Caused by the Concomitant Utilization of Methylene Blue and Venlafaxine in an Oncological Patient. (October 2020) - Gilbert, Brian; Akamune, Inyang E.
Although the interaction between methylene blue and serotonin reuptake inhibitors/serotonin norepinephrine reuptake inhibitors is well documented, there remains a paucity of literature on identifying patient groups who may be at risk for experiencing this interaction. Here, we report a case of methylene blue and venlafaxine-induced serotonin syndrome in a patient with cancer.